2011
DOI: 10.1242/jcs.078733
|View full text |Cite
|
Sign up to set email alerts
|

Condensin phosphorylated by the Aurora-B-like kinase Ark1 is continuously required until telophase in a mode distinct from Top2

Abstract: SummaryCondensin is a conserved protein complex that functions in chromosome condensation and segregation. It has not been previously unequivocally determined whether condensin is required throughout mitosis. Here, we examined whether Schizosaccharomyces pombe condensin continuously acts on chromosomes during mitosis and compared its role with that of DNA topoisomerase II (Top2). Using double mutants containing a temperature-sensitive allele of the condensin SMC2 subunit cut14 (cut14-208) or of top2, together … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
94
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(99 citation statements)
references
References 63 publications
4
94
0
Order By: Relevance
“…Thus, condensin I appears to help generate a signal that delays cytokinesis. Consistent with this view, a subfraction of condensin has also been localized to the spindle midzone in fission yeast (Nakazawa et al 2011). In retrospect, it is no mere coincidence that the original condensin mutants in fission yeast were isolated as those displaying the so-called "cut" phenotype, in which cytokinesis abnormally proceeds without proper segregation of chromosomes (Hirano et al 1986).…”
Section: Coordinating Chromosome Segregation With Cytokinesismentioning
confidence: 81%
See 2 more Smart Citations
“…Thus, condensin I appears to help generate a signal that delays cytokinesis. Consistent with this view, a subfraction of condensin has also been localized to the spindle midzone in fission yeast (Nakazawa et al 2011). In retrospect, it is no mere coincidence that the original condensin mutants in fission yeast were isolated as those displaying the so-called "cut" phenotype, in which cytokinesis abnormally proceeds without proper segregation of chromosomes (Hirano et al 1986).…”
Section: Coordinating Chromosome Segregation With Cytokinesismentioning
confidence: 81%
“…The molecular picture of how the localization and activities of condensin I might be regulated is far from complete, although numerous studies have identified involvement of multiple mitotic kinases, including Cdk1 (Kimura et al 1998;St-Pierre et al 2009), Aurora B (Lipp et al 2007;Collette et al 2011;Nakazawa et al 2011;Tada et al 2011), and Polo-like kinase (St-Pierre et al 2009). Sumoylation has also been implicated in the function of condensin in ribosomal DNA (rDNA) maintenance (Takahashi et al 2008) and kinetochore localization (BachellierBassi et al 2008) in budding yeast.…”
Section: Condensin I Associates With Chromosomes In Prometaphase and mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, these conditional mutants have led to a greater understanding of phage genetics, protein folding, and macromolecular assembly (15)(16)(17). Similarly, cs and ts mutants of different genes essential for cell division, in combination with temperature-shift experiments, have been used to understand the cell cycle phases in which each of these genes act (18).Various changes at the amino acid level or gene regulation level can cause cold sensitivity. Some cs mutants have been suggested to result from altered feedback inhibition of certain metabolic pathways at lower temperatures (19,20).…”
mentioning
confidence: 99%
“…Thus, these conditional mutants have led to a greater understanding of phage genetics, protein folding, and macromolecular assembly (15)(16)(17). Similarly, cs and ts mutants of different genes essential for cell division, in combination with temperature-shift experiments, have been used to understand the cell cycle phases in which each of these genes act (18).…”
mentioning
confidence: 99%